Fourier-transformed infrared spectroscopy study of the ancient ivory tusks from the Sanxingdui site - Li, Xiaoguang; Wang, Chong; Zhang, Yu; Zhang, Ruojing; Li, Sifan; Xiao, Qing; Su, Wen (Frontiers in Earth Science, 2023)
The archaeological site at Sanxingdui preserves a considerable amount of ancient ivory tusks in its artifact pits, and accurately and quantitatively analyzing the original chemical signatures of these ivory tusks is a critical step in interpreting this buried history. In this study, 123 unearthed ivory tusks were characterized using Fourier transformed infrared spectroscopy(FTIR), and seven in-situ heating experiments were conducted. The hydroxylapatite crystallinity and carbonate concentration were quantitatively determined in line with the absorbance peak intensities of the corresponding bands. The average values of splitting factor (SF), type B carbonate/type A carbonate ratio (BC/AC), carbonate/phosphate ratio (C/P), type B carbonate/phosphate ratio (BPI), type A carbonate/phosphate ratio (API), and water-amide on the phosphate index (WAMPI) were calculated to be 3.84, 0.98, 0.12, 0.37, 0.38, and 0.11, respectively. The ratios of the 1416 cm-1 to 1454 cm-1 carbonate bands of the ivory tusks were used to quantitatively estimate the different types of carbonate content in the ivory tusks. Heating experiments were designed to simulate the effect of heat on the hydroxylapatite structures. We suggest that the SF and the C/P indices can serve as distinctive preservation indices of ancient ivory tusks as well as the BC/AC index and hydroxyl types.